Pengembangan E-Book Interaktif Berbasis Android Mata Pelajaran Layanan Lembaga Keuangan Syariah - Ananda Putri Dianti; Luqman Hakim (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The changing of times have reduced the boundary between digital world and physical world in many fields of human life including education. The revised edition of Kurikulum 2013, which was the last change in the education curriculum in Indonesia, must always be balanced with the development of learning tools including teaching materials. This research and development is aimed to develop teaching materials in interactive e-books form based on android devices with a scientific approach to the subject of Islamic financial services in class XII semester 1. This development uses the 4D model belonging to Thiagarjan, Semmel, and Semmel which consists of the stage define, design, develop, and disseminate. However, due to the limitations of the researcher, the research focused on the development stage and implemented the dissemination on a limited basis. The result of this study in feasibility test by a material, linguist, graphical, and stundents’ responses to the use of e-book. From those results, it is known that android based interactive e-book with scientific approach are very suitable for use for learning activities.